2013
DOI: 10.1080/13532944.2013.801675
|View full text |Cite
|
Sign up to set email alerts
|

Bringing voters back in leader selection: the open primaries of the Italian Democratic Party

Abstract: According to the penalty hypothesis, primaries are considered damaging for parties because of the social and political distinctiveness of the electorate, who usually choose unpalatable candidates for the median voter in general elections. This article deals with two leader selections organised by the Italian Partito Democratico (PD) in 2007 and 2009. Using survey data, voters' characteristics in the two primaries relating to the 2008 parliamentary elections are contrasted in order to find out the differences b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…This is broadly pertinent to a more general trend towards personalization of electoral campaigns, with their growing emphasis on leadership appeals (McAllister, 2007). Although cross-national comparative research has shown a significant tendency towards the adoption of more open methods in nominating party candidates for public office, especially through the use of primary elections (Hazan and Rahat, 2010), political parties in several democracies have given their members a role in leadership selection too (Denham, 2009;Kenig, 2009;Lisi, 2010;Cross and Blais, 2012a;Pilet and Cross, 2014;Seddone and Venturino, 2013). Despite of the fact that these developments may vary across countries and across parties, they may be regarded as 'a clear trend in Western political parties' (Wauters, 2015: 218).…”
mentioning
confidence: 99%
“…This is broadly pertinent to a more general trend towards personalization of electoral campaigns, with their growing emphasis on leadership appeals (McAllister, 2007). Although cross-national comparative research has shown a significant tendency towards the adoption of more open methods in nominating party candidates for public office, especially through the use of primary elections (Hazan and Rahat, 2010), political parties in several democracies have given their members a role in leadership selection too (Denham, 2009;Kenig, 2009;Lisi, 2010;Cross and Blais, 2012a;Pilet and Cross, 2014;Seddone and Venturino, 2013). Despite of the fact that these developments may vary across countries and across parties, they may be regarded as 'a clear trend in Western political parties' (Wauters, 2015: 218).…”
mentioning
confidence: 99%
“…However, this method fails to differentiate changes that are the result of contagion, from those driven by coincidence or convergence. The second, perhaps more reliable method of establishing contagion is to discover the motivations and sources of inspiration for parties in implementing organisational reforms (Gauja 2012;Seddone and Venturino 2013;Wauters 2014, 71). These might be sourced from interviews, official party documents (such as reviews), media releases and statements, and political biographies.…”
Section: Policy Transfer and Party Organisational Changementioning
confidence: 99%
“…Another main area of research on leadership selection processes is dedicated to the analysis of their effects . Broadly speaking, five types of effects (Rahat and Hazan, 2001) can be distinguished (which have all been studied recently): participation including the type of participants and turnout rates (Seddone and Venturino, 2013; Wauters, 2015), competitiveness (Kenig, 2009), responsiveness (Lehrer, 2012), representation, in particular the presence of women party leaders (O’Brien, 2015; Wauters and Pilet, 2015), and performance. In this article, we focus on the last type of effects, that is, the effect of leadership selection on performance.…”
Section: Consequences Of Inclusive Leadership Contestsmentioning
confidence: 99%